Zebrafish mutants reveal unexpected role of Lrp5 in osteoclast regulation - Khrystoforova, Iryna; Shochat-Carvalho, Chen; Harari, Ram; Henke, Katrin; Woronowicz, Katherine; Harris, Matthew P.; Karasik, David (Frontiers in Endocrinology, 2022)
Low-density Lipoprotein Receptor-related Protein 5 (LRP5) functions as a co-receptor for Wnt ligands, controlling expression of genes involved in osteogenesis. In humans, loss-of-function mutations in LRP5 cause Osteoporosis-Pseudoglioma syndrome, a low bone mass disorder, while gain-of-function missense mutations have been observed in individuals with high bone mass. Zebrafish (Danio rerio) is a popular model for human disease research, as genetic determinants that control bone formation are generally conserved between zebrafish and mammals. We generated lrp5- knock-out zebrafish to study its role in skeletogenesis and homeostasis. Loss of lrp5 in zebrafish leads to craniofacial deformities and low bone mineral density (total body and head) at adult ages (3 and 6 months old). To understand the mechanism and consequences of the observed phenotypes, we performed transcriptome analysis of the cranium of adult lrp5 mutants and siblings. Enrichment analysis revealed upregulation of genes significantly associated with hydrolase activity: mmp9, mmp13a, acp5a. acp5a encodes Tartrate-resistant acid phosphatase (TRAP) which is commonly used as an osteoclast marker, while matrix metalloprotease 9, mmp9, is known to be secreted by osteoclasts and stimulate bone resorption. These genes point to changes in osteoclast differentiation regulated by lrp5. To analyze these changes functionally, we assessed osteoclast activity in mutants and observed significantly larger resorption areas, increased TRAP staining, and developmental skeletal dysmorphologies in the mutant, suggesting higher activity of osteoclasts in the absence of Lrp5 signaling. Our findings suggest a role of Lrp5 in maintaining bone mineral density and revealed unexpected insights into the function of lrp5 in bone homeostasis through moderation of osteoclast activity.